Pengenalan Manajemen Keuangan Dalam Bentuk Investasi Keuangan Pada Karang Taruna Remaja 009, Kelurahan Gaga, Kecamatan Larangan - Ananda Hadistia; Indri Kharisma; Ardi Bachtiar (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2022)
The purpose of this Community Service activity is to implement one of the Tri Dharma of Higher Education. Besides that, it is also to foster creativity, independence and be able to manage financial self properly and be more focused for Youth Youth Organizations 009, Larangan Tangerang by introducing financial management in the form of financial reports and providing knowledge about investment and how to choose investment applications that are easy and convenient. simple for beginners, especially youth youth groups 009. The method of implementing Community Service used is training, counseling, question and answer and discussion as well as sharing experiences. The technique of implementing Community Service activities used is through virtual meetings using Gmeet software and discussions as well as questions and answers with the number of participants 15 (fifteen) teenagers from Youth Youth Organization 009. Tangerang Prohibition. The output of this Community Service activity is in the form of publications on online media and one scientific article published through the Lokabmas Kreativ PKM Pamulang University. As well as increasing knowledge and understanding the basics of managing finances, increasing knowledge about the types of investments and how to choose investment applications that are easy for beginners